PENERAPAN MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Ai Diniah (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2020)
This study aims to improve the learning outcomes of students in class IX-B MTs Negeri 5 Garut in Mathematics subject matter numbers exponential and root form. This type of research is a classroom action research conducted in two cycles, each of which is carried out in 2 meetings. Each meeting consists of the planning, action, observation and reflection stages. The subjects in this study were all students of class IX-B MTs Negeri 5 Garut in the odd semester of the 2018-2019 school year, totaling 22 students. The data obtained in this study included: learning outcomes and student learning completeness which were taken from giving test questions at the end of each meeting and the activeness of students in the learning process. From the research data, it was obtained that the average learning outcomes of students in cycle I was 80 and cycle II was 95. The average completeness of learning in cycle I was 73% and cycle II was 100%. From these data it is clear that from cycle I to cycle II there is a significant increase. From this research, it is concluded that by using the cooperative learning model the type of teams games tournament (TGT) can improve the learning outcomes of class IX-B students of MTs Negeri 5 Garut in Mathematics subject matter numbers exponential and root form.